Enhancing Emission and Stability in Na-Doped Cs3Cu2I5 Nanocrystals - Na Guo; Lili Liu; Guilong Cao; Shurui Xing; Jingying Liang; Jianjun Chen; Zuojun Tan; Yuequn Shang; Hongwei Lei (Nanomaterials, 2024)
Lead-free Cs3Cu2I5 metal halides have garnered significant attention recently due to their non-toxic properties and deep-blue emission. However, their relatively low photoluminescence quantum efficiency and poor stability have limited their applications. In this work, sodium iodide (NaI) is used to facilitate the synthesis of Cs3Cu2I5 nanocrystals (NCs), demonstrating improved photoluminescence intensity, photoluminescence quantum yield, and stability. Systematic optoelectronic characterizations confirm that Na+ is successfully incorporated into the Cs3Cu2I5 lattice without altering its crystal structure. The improved Photoluminescence Quantum Yield (PLQY) and stability are attributed to the strengthened chemical bonding, which effectively suppresses vacancy defects in the lattice. Additionally, light-emitting diodes (LEDs) based on 10% NaI-doped Cs3Cu2I5 NCs were assembled, emitting vibrant blue light with a maximum radiant intensity of 82 lux and Commission Internationale de l’Eclairage (CIE) chromaticity coordinates of (0.15, 0.1). This work opens new possibilities for commercial lighting display applications.